2022
DOI: 10.1177/00405175221144773
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of soft drafting system and the conventional drafting system based on the ring spinning frame

Abstract: A modified drafting system, named the soft drafting system, based on the ring spinning frame, has been introduced in the previous paper. In order to compare with the conventional drafting system, this paper analyzed pressure distributions of the two drafting systems and compared apron slippages based on the condition of spinning 18.2 tex combed cotton yarns. The results show that the floating area of the soft drafting system is only 6 mm, much smaller than that of the conventional drafting system at 12 mm. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Research showed the mechanism of fibre strand condensing on the drafting zone of the ring frame with compact attachment for the compact yarn by changing the applied pressure and the speed of condensing through different lateral positions of the groove [34]. Another study showed the effect of modified soft drafting on the impact of 18.2 Tex cotton combed yarn to reduce the imperfections on that yarn [5]. Moreover, the study was conducted on the fibre migration properties of cotton and nano fibrehttps://doi.org/10.31881/TLR.2024.068 based compact yarn through the usual ring frame drafting system [35].…”
Section: Potential Research Gapsmentioning
confidence: 99%
See 4 more Smart Citations
“…Research showed the mechanism of fibre strand condensing on the drafting zone of the ring frame with compact attachment for the compact yarn by changing the applied pressure and the speed of condensing through different lateral positions of the groove [34]. Another study showed the effect of modified soft drafting on the impact of 18.2 Tex cotton combed yarn to reduce the imperfections on that yarn [5]. Moreover, the study was conducted on the fibre migration properties of cotton and nano fibrehttps://doi.org/10.31881/TLR.2024.068 based compact yarn through the usual ring frame drafting system [35].…”
Section: Potential Research Gapsmentioning
confidence: 99%
“…Then, by the yarn count tester or a simple wrap reel and a digital weight scale, the yarn count in Ne is obtained. Finally, the CSP value is obtained by multiplying this force value in lbs by the yarn count value in Ne [5].…”
Section: Count Strength Product (Csp)mentioning
confidence: 99%
See 3 more Smart Citations